Computation of the scattered fields from an arbitrary discontinuity on a perfectly conducting ground plane by a decomposition method - Saynak, Ugur; Kizilay, Ahmet (Tubitak Scientific & Technological Research Council Turkey, 2016)
A novel procedure for solving plane wave incident on arbitrary bump or cavity geometries on a perfectly conducting ground plane is introduced. The method is presented with examples for transverse-magnetic polarization compared to various other solution methods. The proposed method can be easily generalized to other similar problems.
Keywords: Perturbation methods; method of moments; computational electromagnetics; rough surfaces; ELECTROMAGNETIC SCATTERING; INTEGRAL-EQUATIONS; TM-SCATTERING; GROOVE; CAVITY; TROUGH; Computer Science; Engineering